Integrated tool for assessing sustainability index of distillation column systems - Nordin, Mohamad Zulkhairi (Taylor's University, 2015)
This paper presents the application of the integrated tool for assessing the sustainability index of distillation column systems. Sustainability tool was developed to assess and improve the sustainability of a process. However, the current developed sustainability tools are only based on the one-dimension analysis. In this study, a new integrated tool for assessing sustainability index of distillation column systems is developed. The advantage of this tool is that the calculation of the sustainability index will consider three different indices simultaneously, which are one-dimension, two-dimension and three-dimension indices. By using the developed tool, the comparison between those three types of sustainability indices can be done in an easy and systematic manner. The framework of the developed integrated sustainability tool consists of four parts: introduction, components selection, data input and analysis. The objective of the first part is to introduce the user to the distillation column process. Then, the users have to select components which are involved in the process in the second part. Next, in the third part the users need to key in the necessary data, such as feed and product flow rates and composition, energy for condenser and reboiler, and others required data. The fourth part is the analysis part, which the objective is to analyse and display the calculated value of the sustainability indices. The application of this tool is illustrated using the separation of benzene and toluene with a single distillation column. The data required for the tool was obtained from the highest point of the driving force that used to design the distillation column. It is shown that the tool able to analyse three different sustainability indices simultaneously in easy and systematic manner